Enhancing solar thermal desalination with MWCNT/TiO2 nanofluids for sustainable water solutions - T. Sathish; R. Saravanan; Jayant Giri; Refka Ghodhbani; Hassen Sabeur; Mustafa Abdullah; A. Anderson (Case Studies in Thermal Engineering)
This study uses innovative humidifier-dehumidifier (HDH) combinations with evacuated tube solar collector (ETSC) and flat air collector (FAC) coupled with multiwalled carbon nanotubes, and titanium oxide (MWCNT/TiO2) hybrid nanofluid and hybrid nano-enhanced coating to maximize sustainable saltwater drinking water production. Desalination humidifiers and dehumidifiers (HDH) evaporate and condense saltwater to remove salt. This research used HDH with an ETSC and FAC to desalinate saltwater using a heat exchanger. ETSC and FAC systems used water and air as major fluids. The multiwalled carbon nanotubes (MWCNT) and titanium dioxide (TiO2) nanoparticles were added at 0.1 % each to generate a 50:50 hybrid nanofluid to improve ETSC working fluid thermal characteristics. To maximize absorptivity, the FAC system mixes black paint with MWCNT and TiO2 nanoparticles for absorber coating. A hybrid MWCNT/TiO2 nano-enhanced coating (hybrid nanoparticles combined with black paint) increased thermal performance. Using nanofluid and nanocoating in ETSC and FAC improved thermal performance over water alone and non-coating. In particular, the ETSC hybrid MWCNT/TiO2 nanofluid had peak fluid temperature, input heat to HDH, humidifier efficiency, and water productivity of 73.4 °C, 324.6W, 67.3 %, and 799.7 mm3/h. Hybrid MWCNT/TiO2 nano-enhanced coating increased humidifier efficiency by 70.8 % and water production by 806.4 mm3/h.